Maintaining Creativity and Ensuring Research: Teaching Creative Research in Film and Media Arts. A Personal Reflection. (International Journal on Stereo & Immersive Media, 2025)
Current article is a reflection of a personal journey of transitioning from an artistic research track PhD student to a supervisor and lecturer helping the others in navigating the confusing and promising seas of artistic research. In 2020, I was the first PhD student to defend my thesis on the artistic research track of the /Anonymised/ School and as soon as I had defended, I was asked to serve in the position of the head of artistic research the track. As such, I experienced the trials and tribulations of the beginnings first hand and am now in a unique position to reflect upon the challenges we faced. As I write this, the two separate tracks of research in /Anonymised/ School have been merged into one, but as the period I experienced it, they were still separate, my reflection builds upon the previous structure.